Comparative evaluation of round window niche accessibility pre-operatively on high-resolution computed tomography of the temporal bone with intra-operative findings. Issue 7 (28th June 2019) - Sharma, R; Meher, R; Passey, J C; Kumar, J; Gupta, A; Kharbanda, S
Abstract: Objective: To compare round window niche visibility as seen endoscopically during cochlear implant surgery with pre-operative high-resolution computed tomography of the temporal bone. Methods: Nineteen patients scheduled for cochlear implantation, aged 2–20 years, were referred for computed tomography from October 2016 to March 2018. Angles were measured between the lines passing through the mid-sagittal plane and cochlear basal turn on the scans. Endoscopic round window niche visibility during posterior tympanotomy was categorised as: type I = 100 per cent, type IIa = more than 50 per cent, type IIb = less than 50 per cent or type III = 0 per cent. Pre-operative computed tomography measurements were used to predict round window niche visibility before surgery and correlated with intra-operative findings. Results: The mean (range) of pre-operative angles on computed tomography for endoscopic visibility types I, IIa and IIb, were 64.06° (61.16–69.37°), 63.81° (58.61–71.35°) and 56.48° (50.37–59.05°), respectively, a statistically significant finding (one-way analysis of variance test, p = 0.016). Conclusion: Pre-operative high-resolution temporal bone computed tomography measurements are useful in predicting round window niche visualisation as viewed endoscopically during posterior tympanotomy. The angle was more acute in type IIb compared to type I.